Quality of Life and Patient-Reported Outcomes in Breast Cancer Survivors: A Multicenter Comparison of Four Abdominally Based Autologous Reconstruction Methods. Issue 3 (March 2016) - Macadam, Sheina A.; Zhong, Toni; Weichman, Katie; Papsdorf, Michael; Lennox, Peter A.; Hazen, Alexes; Matros, Evan; Disa, Joseph; Mehrara, Babak; Pusic, Andrea L.
Abstract : Background: Approximately 20 percent of women select autologous tissue for postmastectomy breast reconstruction, and most commonly choose the abdomen as the donor site. An increasing proportion of women are seeking muscle-sparing procedures, but the benefit remains controversial. It is therefore important to determine whether better outcomes are associated with these techniques, thereby justifying longer operative times and increased costs. Methods: Patients from five North American centers were eligible if they underwent reconstruction by means of the deep inferior epigastric artery perforator (DIEP) flap, muscle-sparing free transverse abdominis myocutaneous (TRAM) flap, free TRAM flap, or the pedicled TRAM flap. Patients were sent the BREAST-Q. Demographics and complications were collected. Results: The authors analyzed 1790 charts representing 670 DIEP, 293 muscle-sparing free TRAM, 683 pedicled TRAM, and 144 free TRAM patients with an average follow-up of 5.5 years. Flap loss did not differ by flap type. Partial flap loss was higher in pedicled TRAM compared with DIEP ( p = 0.002). Fat necrosis was higher in pedicled TRAM compared with DIEP and muscle-sparing free TRAM ( p < 0.001). Hernia/bulge was highest in pedicled TRAM ( p < 0.001). Physical well-being (abdomen) scores were higher in DIEP compared with pedicled TRAM controlling for confounders. Conclusions: Complications and patient-reported outcomes differ when comparing abdominally based breast reconstruction techniques. The results of this study show that the DIEP flap was associated with the highest abdominal well-being and the lowest abdominal morbidity compared with the pedicled TRAM flap, but did not differ from muscle-sparing free TRAM and free TRAM flaps. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, III.